2018
DOI: 10.18203/2394-6040.ijcmph20180743
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of oral healthcare among pregnant women in Assiut, Egypt

Abstract: Background: Pregnancy is an important time in a woman's life with many complex physiological changes that may occur. These changes may negatively affect their oral health. The study aimed to assess oral health knowledge, attitude and reported practices among pregnant women in Assiut Governorate.Methods: A descriptive cross-sectional study design was used. A structured interview questionnaire was used; included two tools: Tool (I); part (1) personal data, part (2): assessment of knowledge about oral health, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 10 publications
0
19
0
2
Order By: Relevance
“…15 This is following several studies that conclude that good practice does not always follow good knowledge, but several factors influence education level, work, and resi-dence. 16,17,18 The Community Health Centre (Puskesmas) is a first-level health service facility that prioritises promotional and preventive efforts. 19 Promotional efforts of Sukajadi Community Health Centre, including several programs, including Integrated Health Service (Posyandu), School Dental Care (UKGS), and Village Midwife Clinic (Polindes).…”
Section: Introductionmentioning
confidence: 99%
“…15 This is following several studies that conclude that good practice does not always follow good knowledge, but several factors influence education level, work, and resi-dence. 16,17,18 The Community Health Centre (Puskesmas) is a first-level health service facility that prioritises promotional and preventive efforts. 19 Promotional efforts of Sukajadi Community Health Centre, including several programs, including Integrated Health Service (Posyandu), School Dental Care (UKGS), and Village Midwife Clinic (Polindes).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that 85.9% used a toothbrush to clean their teeth. 8 In the present study, it was observed that 97.6% of the interviewed antenatal mothers used a toothbrush and 41.8% answered that teeth should be daily cleaned to prevent food from getting stuck in the teeth; 15.3% believed that gum diseases can be avoided by regular brushing of teeth and 40% brushed their teeth daily to avoid bad breath while 2.9% did not about the importance of regular brushing of teeth.…”
Section: Discussionmentioning
confidence: 54%
“…Hormonal changes during pregnancy along with neglected oral hygiene often lead to gingivitis and periodontitis in the antenatal mothers. 8 The physiological increase in plasma volume results in urine concentration and about 70 % of pregnant women develop glycosurea which facilitates bacterial growth in urine. Thus genital hygiene during pregnancy is to be stressed as pregnancy enhances the progression from asymptomatic to symptomatic bacteriuria which may lead to pyelonephritis and obstetric outcomes like prematurity, low birth weight and increased neonatal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Other reasons for the low utilization could be lack of emphasis from their antenatal care providers, fear that the treatment can be harmful to the fetus and financial burden. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%